2005
DOI: 10.1002/bit.20547
|View full text |Cite
|
Sign up to set email alerts
|

Efficient one‐step production of astaxanthin by the microalga Haematococcus pluvialis in continuous culture

Abstract: The performance of Haematococcus pluvialis in continuous photoautotrophic culture has been analyzed, especially from the viewpoint of astaxanthin production. To this end, chemostat cultures of Haematococcus pluvialis were carried out at constant light irradiance, 1,220 μE/m2 · s, and dilution rate, 0.9/d, but varying the nitrate concentration in the feed medium reaching the reactor, from 1.7 to 20.7 mM. Both growth and biomass composition were affected by the nitrate supply. With saturating nitrate, the biomas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
0
1

Year Published

2007
2007
2013
2013

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 99 publications
(45 citation statements)
references
References 29 publications
2
42
0
1
Order By: Relevance
“…Analysis of variance confirmed that together with a large influence of the nitrate supply (Del Río et al, 2005), the irradiance could also have a marked enhancing effect on the accumulation of astaxanthin by Haematococcus cells in continuous culture. This behavior became also apparent by plotting the astaxanthin content of the biomass from 43 different cultures maintained under steady state conditions versus the specific nitrate input, the data being grouped in four separate series corresponding to different average irradiance ranges (Fig.…”
Section: Astaxanthin Accumulationmentioning
confidence: 79%
See 3 more Smart Citations
“…Analysis of variance confirmed that together with a large influence of the nitrate supply (Del Río et al, 2005), the irradiance could also have a marked enhancing effect on the accumulation of astaxanthin by Haematococcus cells in continuous culture. This behavior became also apparent by plotting the astaxanthin content of the biomass from 43 different cultures maintained under steady state conditions versus the specific nitrate input, the data being grouped in four separate series corresponding to different average irradiance ranges (Fig.…”
Section: Astaxanthin Accumulationmentioning
confidence: 79%
“…Besides representing an efficient and simple production process, the fact that the growing and dividing cell population exhibited active astaxanthin accumulation demonstrated that such ability neither required encystment nor was a property unique to non-growing cells, as assumed by others (Borowitzka et al, 1991;Boussiba, 2000;Boussiba et al, 1999;Fábregas et al, 2001;Harker et al, 1996;Kobayashi et al, 1997). A preliminary assessment of the one-step system yielded a considerably high productivity, of 5.6 mg astaxanthin/L day (Del Río et al, 2005). Notwithstanding, productivity and efficiency of the one-step system versus the two-stage counterpart have recently been challenged by Aflalo et al (2007), on the ground that 'there is no real biotechnological advantage to vigorously growing cells for production of the secondary carotenoid astaxanthin.…”
Section: Introductionmentioning
confidence: 79%
See 2 more Smart Citations
“…Presenta un color rojo-anaranjado por lo que se utiliza para pigmentar el salmón, truchas, crustáceos y algunas aves. Además, posee mayor actividad antioxidante que la vitamina E, debido a esto se utiliza en productos nutracéuticos y cosméticos (Higuera-Ciapara et al, 2006;Del Río et al, 2005).…”
Section: Ja Núñez-gastélum DI Sánchez-machado J López-cervanteunclassified